2011
DOI: 10.1074/jbc.m111.220525
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor (PPAR) Gene Profiling Uncovers Insulin-like Growth Factor-1 as a PPARα Target Gene in Cardioprotection

Abstract: Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear receptor family of ligand-activated transcription factors and consist of the three isoforms, PPAR␣, PPAR␤/␦, and PPAR␥. Considerable evidence indicates the importance of PPARs in cardiovascular lipid homeostasis and diabetes, yet the isoform-dependent cardiac target genes remain unknown. Here, we constructed murine ventricular clones allowing stable expression of siRNAs to achieve specifically knockdown for each of the PPAR isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
2
24
0
2
Order By: Relevance
“…Fourth, IGF-I plays a main role in restoring mitochondrial dysfunction during aging by increasing mitochondrial membrane potential, reducing oxygen consumption, and increasing ATP synthesis, which in turn minimize the cytochrome release to the cytoplasm and subsequently promote neural survival by decreasing caspase-induced apoptosis [35]. Azzouzi et al [36] confirmed the role of the IGF-I signaling pathway in the protection of cardiomyocytes under ischemic and hemodynamic loading conditions. Impaired IGF-I signaling has already been linked to increased oxidative stress and mitochondrial dysfunction in neuronal cells [37].…”
Section: Discussionmentioning
confidence: 97%
“…Fourth, IGF-I plays a main role in restoring mitochondrial dysfunction during aging by increasing mitochondrial membrane potential, reducing oxygen consumption, and increasing ATP synthesis, which in turn minimize the cytochrome release to the cytoplasm and subsequently promote neural survival by decreasing caspase-induced apoptosis [35]. Azzouzi et al [36] confirmed the role of the IGF-I signaling pathway in the protection of cardiomyocytes under ischemic and hemodynamic loading conditions. Impaired IGF-I signaling has already been linked to increased oxidative stress and mitochondrial dysfunction in neuronal cells [37].…”
Section: Discussionmentioning
confidence: 97%
“…Activation of PPARa by fenofibrate has an anti-cancer effect and attenuates signaling responses of IGF1R in medulloblastoma and glyoma cell lines (Urbanska et al 2008, Drukala et al 2010. In contrast, PPARa activation in the heart, through Wy-14643 administration, results in upregulation of Igf1 expression in myocytes and subsequent protection against ischemia/reperfusion-induced apoptosis (El Azzouzi et al 2011). A possible explanation is that either fenofibrate or Wy-14643 acts on the IGF1 system in a PPARa-independent manner.…”
Section: Discussionmentioning
confidence: 83%
“…This signalling loop can be potentially responsible for epigenetic activity that targets survival, proliferation and/or differentiation of cardiac cells. Physical effort has been shown to increase levels of IGF-I in muscle and physiological cardiac hypertrophy, thus inducing the IGF-I/ PI3K/Akt/P70S6K signalling pathway, and thereby increasing the protein synthesis required to build muscle; all of this can be epigenetically regulated [34,60,153,154]. On the other hand, PPAR-c ligands (such as rosiglitazone) activate tuberous sclerosis complex-2 (TSC2) inhibiting mTOR signalling [152,155] intrauterine growth restriction (IUGR), where a decrease in postnatal IGF-I mRNA variants is associated with histone 3 tri-methylation of lysine 36 at the igf1 gene (H3Me3K36).…”
Section: Igfs and Histonesmentioning
confidence: 99%